2017
DOI: 10.1038/srep41857
|View full text |Cite
|
Sign up to set email alerts
|

Novel Protective Role of Myeloid Differentiation 1 in Pathological Cardiac Remodelling

Abstract: Myeloid differentiation 1 (MD-1), a secreted protein interacting with radioprotective 105 (RP105), plays an important role in Toll-like receptor 4 (TLR4) signalling pathway. Previous studies showed that MD-1 may be restricted in the immune system. In this study, we demonstrated for the first time that MD-1 was highly expressed in both human and animal hearts. We also discovered that cardiac-specific overexpression of MD-1 significantly attenuated pressure overload-induced cardiac hypertrophy, fibrosis, and dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(61 citation statements)
references
References 48 publications
(57 reference statements)
7
54
0
Order By: Relevance
“…In addition, previous researchers have reported that myeloid differentiation 1 attenuated the Ang II‐induced hypertrophy in neonatal rat cardiomyocytes. Xiong et al also showed that the MEK(mitogen‐activated protein kinase kinase)‐ERK 1/2 signalling pathway was involved in the antihypertrophic effect under Ang‐II stimuli . These results are consistent with our findings.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, previous researchers have reported that myeloid differentiation 1 attenuated the Ang II‐induced hypertrophy in neonatal rat cardiomyocytes. Xiong et al also showed that the MEK(mitogen‐activated protein kinase kinase)‐ERK 1/2 signalling pathway was involved in the antihypertrophic effect under Ang‐II stimuli . These results are consistent with our findings.…”
Section: Discussionsupporting
confidence: 93%
“…Recent evidences suggested that RP105 attenuates ischaemia/reperfusion‐induced myocardial injury via suppressing the activation of the TLR4/NF‐κB signalling pathway . Our research term also have proved that MD1 negatively regulated MEK‐ERK1/2 and NF‐κB signalling pathways and rescued the adverse effects on pressure‐overload induced cardiac remodelling . Thus, we also check the activities of MAPK and NF‐κB signalling in our study.…”
Section: Discussionsupporting
confidence: 65%
“…Another study found that MD1 deficiency played an important role in accelerating the development of inflammatory atrial fibrosis and increasing vulnerability to AF in mice with HFD‐fed induced obesity . In our previous research, we have verified MD‐1 is a vital modulator of cardiac hypertrophy and fibrosis . Thus, we hypothesized that MD‐1 may also play vital effects in obesity‐induced cardiomyopathy.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations